CADAR DAN RADIKALISME TINJAUAN KONSEP ISLAM RADIKAL YUSUF QARDHAWI - Hakim, Abdurrahman (Universitas Islam Negeri Raden Intan Lampung, 2020)
This paper aims to respond the social phenomena which is viral in the society lately. In the social life of society, a veiled women be suspected a member of radical understanding. At the same time, the legal verse about veil in the Quran debated again because there are differences of opinion between past Muslim scientists and presents Muslim scientists. Finally, the social groups in society divided into support and repellent group about the goverment plan to ban the use of veils in Indonesia. The research methods used in this paper are the qualitative-descriptive methods with library research category. The research data used be optained from a journal, website, book and social media. Next, the research date will be analyzed using Islamic radicalism theories by Yusuf Qardhawi. To answer the main topic of this article, the author will identify about veil included in the criteria of adherents to radical understanding or not.